A circular construction evaluation framework to promote designing for disassembly and adaptability. (20th September 2021) - Dams, Barrie; Maskell, Daniel; Shea, Andrew; Allen, Stephen; Driesser, Marten; Kretschmann, Tom; Walker, Pete; Emmitt, Stephen
Abstract: This paper formulates a concise, free-to-use Circular Construction Evaluation Framework (CCEF) based upon international design code guidelines to assess and quantify the circularity credentials of an existing or proposed construction project. Central to the principles of circular construction is designing for disassembly and adaptability - the ability of a building's elements and connecting components to be disassembled and reused, or rearranged, after the initial design life. Analysis of modern methods of construction and the compatibility of systems with the concepts of designing for disassembly and material reuse inform the development of the CCEF. Circular construction is facilitated by simplicity, standardisation and modularity in design, sustainably-sourced materials, transparent and accessible mechanical connections and the adoption of a manufacturing-style approach towards durable and reusable standardised components and materials. The CCEF allows users such as clients, consultants, contractors, local and national planning and infrastructure policy professionals to evaluate both whole building and elemental levels at the early design and planning stages in a new-build, refurbishment or renovation project. Implementation of a scoring system is demonstrated by the evaluation of example buildings with varying usage of conventional and bio-based materials. It is shown by use of the framework that a simple standardised construction using reversible connections and previously used material elements rates highly, demonstrating a greater extent of circularity in the construction. Highlights: A concise circular evaluation framework specifically for construction projects. International standards and a range of literature inform the basis of the framework. Existing LCA-based product systems can be complex and expensive. Framework intended to inform construction projects at planning and early design stages. Simple modular design, dry reversible connections and material reuse score highly.